Health care professionals’ attitudes towards youth-friendly sexual and reproductive health services in Jordan: a cross-sectional study of physicians, midwives and nurses - Gausman, Jewel (Reprod Health, 2021)
BACKGROUND: Youth-friendly sexual and reproductive health (SRH) services are thought to make such services for adolescents more accessible and acceptable; however, provider attitudes may still present an important barrier. Improving youth SRH service utilization has been recognized as a national priority in Jordan; however, existing services remain underutilized. Previous studies found that youth perceive SRH services to be inadequate and that providers are not supportive of their needs. The purpose of this study is measure provider attitudes towards youth-friendly SRH services and explore their variation according to individual characteristics among health care professionals in Jordan. METHODS: We measured provider attitudes towards youth-friendly SRH services using a scale that was developed and validated in Jordan. The scale consists of three subscales: (1) Attitudes towards SRH information and services offered to youth, (2) Norms and personal beliefs, and (3) Attitudes towards the policy and clinical environment. Possible scores range between 1 and 4, with higher scores reflecting more youth-friendly attitudes. Physicians, midwives and nurses working at either primary health centers, comprehensive care centers, or women’s and children’s health centers where services to adolescents are or should be offered were recruited from four governorates in Jordan using a two-stage, cluster sampling scheme. Differences in attitudes were assessed using simple and multivariable linear regression analysis. RESULTS: The sample consisted of 510 providers from four governorates in Jordan. The mean provider score on the full scale was 2.7, with a range of 2.0 to 3.8. On Subscales 1 and 2, physicians exhibited significantly more youth-friendly attitudes than nurses by scoring 0.17 points higher than nurses on Subscale 1 (95% CI: 0.02–0.32; p < 0.05) in adjusted analyses. Providers who had been previously trained in SRH issues scored 0.10 points higher (95% CI: 0.00—0.20; p < 0.05) than those who had not on Subscale 3. No differences were found according to provider characteristics on Subscale 2. Providers exhibited the lowest scores related to items referencing youth sexual behavior. CONCLUSIONS: Provider attitudes towards youth-friendly SRH service delivery highlight context-specific, cultural concerns. The limited variation in attitudes related to norms and personal beliefs may be a reflection that such beliefs are deeply held across Jordanian society. Last, as past training on SRH was significantly associated with higher scores, our results suggest opportunity for intervention to improve providers’ confidence and knowledge.